KEMAMPUAN PIGMEN KAROTEN DAN XANTOFIL MIKROALGA Porphyridium crunetum SEBAGAI ANTIOKSIDAN PADA DOMBA - Agustini, Ni Wayan Sri (Sekretariat Badan Penelitian dan Pengembangan Pertanian, 2017)
ABSTRAK. Xanthophyll and carotene is a carotenoid group that has potential as an antioxidant and has been reported carotenoids can be synthesized by microalgae P. cruentum. This study aimed to test the potential carotene and xantofil of P. cruentum as an antioxidant, by measuring of malondialdehyde (MDA) and superoxide dismutase (SOD) on sheep red blood cells by oxidative stress. Measurement of MDA using the thiobarbituric acid reactive substance (TBARS) which is based on the reaction between two molecules of TBA with one molecule under acidic conditions. SOD activity measurements with Adenochrom Assay method that is based on the ability of SOD inhibits autooxidation of epinephrine under alkaline conditions. Concentration of carotene used is 0.6; 6; 60 mg/mL and a positive control (vitamin E), while the concentration of xantophyl was 0.8; 8; 80 mg/mL and a positive control (vitamin C).The results showed that MDA levels in sheep red blood cells given carotene pigment were 0.78 ± 0.02 nmol/ml (0.6 μg/mL); 0.34 ± 0.04 nmol/mL (6 μg/mL); 0.15 ± 0.04 (60 μg/mL), and those given xantophyll pigment were 0.64 ± 0.04 nmol/mL (0.8 μg/ml); 0.6 ± 0.06 nmol/mL (8 μg/mL); 0.52 ± 0.04 nmol/mL (80 μg/mL).While the activity of SOD on sheep red blood cells given carotene pigment are 31.53 ± 1.98 unit/mL (0.6 μg/mL); 39.16 ± 1.2 (6 μg/mL); 48.1 ± 0.46 unit/mL (60 μg/mL) and given xantophyll pigment of 29.17 ± 1.2 unit/mL (0.8 μg/ml); 37.32 ± 0.79 unit/mL (8 μg/mL); 42.58 ± 1.2 unit/mL (80 μg/mL). The result of statistical test using SPSS 16 concluded that use of carotene and xantophyllin sheep red blood cell that were given oxidative stress can decrease MDA level and increase the activity of SOD. This proves that carotene and xantophyll pigments of P. cruentumhave the ability as antioxidant.